Reconhecimento geofísico em aquífero fraturado em Caçapava do Sul (RS): análise comparativa entre arranjos de tomografia elétrica - Bortolozzo, Rômulo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The groundwater exploration is an alternative that has been growing in Brazil, especially in regions that lack surface or peripheral sources to conventional distribution systems. Fractured aquifers consist of complex systems where water percolation occurs through discontinuities such as faults and fractures. The location of productive wells in these environments becomes a major challenge, since most of the resulting wells are dry or have unsatisfactory flow rates. Geophysics comprises a set of indirect subsurface research tools that allow the evaluation of the geological environment through the contrast of physical properties of materials such as electrical resistivity. The geophysical methods have been widely used in hydrogeological studies, mainly through the technique of Electrical Resistivity Tomography (ETR), which allows the detection of fractured zones with aquifer potential from the processing of 2D inversion and 3D visualization models. This work accomplishes a reconnaissance of flow structures in a fractured aquifer in the region of Caçapava do Sul (RS), through the application of the geophysical method of Eletroresistivity through the technique of Electrical Tomography in Dipole-Dipole, Schlumberger and Wenner arrangements. Structural data obtained in massive and unaltered granite outcrops close to the study area served as the basis for a comparative analysis between the models generated for each arrangement in order to define the most appropriate and consistent with the geological reality. The products related to the Schlumberger arrangement, unlike the others, allowed the modeling of a low resistivity surface, which was related to a family of water saturated fractures recognized in the field. The crossing of the structural data with the 3D model of isosurface allowed to indicate a promising place to the abstraction of underground water

A exploração da água subterrânea é uma alternativa que vem crescendo no Brasil, principalmente em regiões desprovidas de fontes superficiais ou periféricas aos sistemas de distribuição convencionais. Os aquíferos fraturados consistem em sistemas complexos onde a percolação de água ocorre através de descontinuidades, como falhas e fraturas. A locação de poços produtivos nestes ambientes torna-se um grande desafio, visto que a maioria dos poços resultantes são secos ou apresentam vazões insatisfatórias. A geofísica compreende um conjunto de ferramentas indiretas de investigação em subsuperfície, que permitem avaliar o meio geológico através do contraste de propriedades físicas dos materiais, como a resistividade elétrica. Os métodos geofísicos têm sido bastante empregados em estudos hidrogeológicos, principalmente por meio da técnica de Tomografia Elétrica de Resistividade (ETR), que possibilita revelar zonas fraturadas com potencial aquífero a partir do processamento de modelos de inversão 2D e de visualização 3D. Este trabalho realiza um reconhecimento de estruturas de fluxo em um aquífero fraturado na região de Caçapava do Sul (RS), através da aplicação do método geofísico de Eletrorresistividade por meio da técnica de Tomografia Elétrica em arranjos Dipolo-Dipolo, Schlumberger e Wenner. Dados estruturais obtidos em exposições de granito maciço e inalterado próximas à área de estudo serviram de base para uma análise comparativa entre os modelos gerados para cada arranjo, a fim de definir o mais adequado e condizente com a realidade geológica. Os produtos referentes ao arranjo Schlumberger, ao contrário dos demais, possibilitaram o modelamento de uma superfície de baixa resistividade, que foi relacionada com uma família de fraturas saturadas em água reconhecida em campo. O cruzamento dos dados estruturais com o modelo 3D de isosuperfície permitiu indicar um local promissor à...
Keywords: Águas subterrâneas; Aquiferos; Geofisica; Hidrogeologia; Caçapava do Sul (RS)